A Psychological Study of Gothic Fiction Based on Post-Traumatic Experiences Case Study: The Protagonist ‘Sethe’ in Tony Morison’s ’Beloved’ - NEDJIMI, Meriem Hiba; SELT ,Djihad Afaf (Faculty of Letters and Foreign Languages Department of English, 2019)
This given dissertation entitled ‘’A Psychological Study of Gothic Fiction Based on Post Traumatic Experiences’’ aims to investigate and target the immense role of the traumatic experiences (especially of slavery as a psychological factor that may reconstruct the black peoples’ personalities and thinking. It attempts to tackle how these people are obliged to undergo the loss of their identities and not only face the brutality of racism, but their own society as well. The protagonist of the novel, Sethe, is a vivid example of the given case. As a black woman, she was distend to have a difficult life as a slave. Her first traumatic experience started at her very young age. Her second traumatic journey started when she killed her own daughter, Beloved, for the sake of saving her from the brutality of life, and the inhumanity in this world. This paper analyzes the effects of the first traumatic experience on the psychological state of mind of Sethe, causing the second trauma, and resulting in severe psychotic and mental disorders and turning maternal instincts from mother’s love into a killer. It also highlights the aftershock of the brutal experiences that is highly seen through the psychotic symptoms in Sethe, such as hallucinations and delusion embodied in the ghostly apparition; Beloved and representing the brutal past of Sethe, intertwined with her present